2017
DOI: 10.1039/c6mt00298f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent activation of Cu,Zn-superoxide dismutase-1

Abstract: Copper zinc superoxide dismutase (Sod1) is a critical enzyme in limiting reactive oxygen species in both the cytosol and the mitochondrial intermembrane space. Sod1 dismutes superoxide anions to hydrogen peroxide and oxygen. The catalytic reaction is dependent on an active site copper ion and a disulfide bonded conformation. The activation of Sod1 is mediated by its chaperone Ccs1. The mechanism of Ccs1-mediated Sod1 activation involves both insertion of the catalytic copper ion and mediating disulfide bond fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 132 publications
0
75
0
Order By: Relevance
“…It has been generally assumed that SOD1 diffusively acquires Zn from the available pool within the cell as the first step in its maturation process (reviewed in Ref. 13). This is supported by the lack of Zn-specific metallo-chaperones that have been discovered, to date, and the fact that WT SOD1 purified from yeast lackingCCS1isdevoidofCu,yetenrichedwithZn(Ͼ1Zn/monomer) (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been generally assumed that SOD1 diffusively acquires Zn from the available pool within the cell as the first step in its maturation process (reviewed in Ref. 13). This is supported by the lack of Zn-specific metallo-chaperones that have been discovered, to date, and the fact that WT SOD1 purified from yeast lackingCCS1isdevoidofCu,yetenrichedwithZn(Ͼ1Zn/monomer) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Without CCS1 present, the population of SOD1 disintegrates into an assorted collection of improperly metallated molecules ranging from completely Zn-free to conformers with 2 Zn ions/monomer (reviewed in Ref. 13)). CCS1 likely plays an all-encompassing faciliatory role during SOD1 activation that starts with guaranteeing "correct" Zn status of the SOD1 molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation is known to increase the production of reactive ROS that induces oxidative damage, and SOD plays an important role in alleviating oxidative stress. However, to the best of our knowledge, no one has studied whether oxidative stress is involved in the development of ORN. Interestingly, we found that increased oxidative stress induced by radiation was significantly attenuated by α2M, suggesting that antioxidation might play some role in the beneficial effects of α2M on ORN during the acute phase after radiation.…”
Section: Discussionmentioning
confidence: 99%
“…62 SOD1 maturation in both the cytosol and the IMS requires the copper chaperone for SOD1 (CCS), which inserts copper into apo-SOD1 and catalyzes the formation of an intermolecular disulphide bond that stabilizes the homodimer and is essential for enzyme activity. 63, 64 The relative distribution of CCS between the cytosol and the mitochondrion is governed by the MIA40-ERV1 disulphide relay system, which oxidizes two cysteines within its first domain to form a disulphide bond that promotes CCS retention within the IMS. 65 Since both SOD1 and CCS are imported into the IMS as apo-proteins, the copper required for the maturation and catalytic activity of SOD1 must also come from the matrix copper pool.…”
Section: Copper In Mitochondriamentioning
confidence: 99%